Cone-Beam Computed Tomography Comparison of Canal Transportation after Preparation with BioRaCe and Mtwo Rotary Instruments and Hand K-Flexofiles - Mokhtari, Hadi; Niknami, Mahdi; Sohrabi, Aydin; Habibivand, Ehsan; Mokhtari Zonouzi, Hamid Reza; Rahimi, Saeed; Zand, Vahid (Iranian Endodontic Journal, 2014)
Introduction: The aim of this in vitro study was to evaluate the transportation of mesiobuccal canals of mandibular first molars prepared with either BioRaCe or Mtwo rotary instruments or hand K-Flexofile, by means of cone-beam computed tomography (CBCT). Methods and Materials: Forty-five mandibular molars were selected and randomly divided into three groups (n=15). Mesiobuccal roots of these teeth were prepared by BioRaCe, Mtwo, or hand K-Flexofile. Transportation was measured by pre- and post-operative CBCT images. Two-way ANOVA analysis was applied to detect any differences between the groups followed by the post hoc Tukey’s tests. The level of significance was set at 0.05. Results: The non-parametric Friedman test was used to compare the behavior of each file at 3-, 6- and 9-mm levels. There were no significant differences between different levels in Mtwo group (P=0.15); however, the differences in K-Flexofile and BioRaCe groups were significant (P>0.05). Post hoc Tukey’s test revealed significant differences between BioRaCe and K-Flexofile and also between Mtwo and K-Flexofile, both in the 3-mm depths (P<0.05). Conclusion: Under the limitations of the present study, BioRaCe and Mtwo rotary instruments are considered suitable for canal preparation to greater apical sizes provided that the recommended sequences are observed.